NORAD in perpetuity and beyond - Charron, Andrea; Fergusson, James G. 1954- (McGill-Queen’s University Press, 2022)
"The North American Aerospace Defense Command (NORAD) has undergone wide-ranging changes since 2006, when it was given a new maritime warning mission and the NORAD Agreement was signed in perpetuity. Andrea Charron and James Fergusson trace NORAD’s recent history, marked by innovations in technology and in command and control, but also by unprecedented threats. The shared defence of North America remains an important issue that should extend to other areas, such as the joint defence of the maritime and cyber domains. Fuelled by a deep curiosity about the command and its decisions made in the face of inevitable geopolitical and technological changes, this book uses a functional lens to evaluate NORAD’s options and the technological and organizational solutions needed to defend North America. The authors investigate the ways in which the NORAD command might adapt in the future as it struggles to modernize and keep ahead of new threats. This book comes at a critical time. The rise of new peer competitors requires a fundamental reconsideration of North American defence. As one of very few contemporary analyses of the command and its future, NORAD will be a vital tool for scholars and practitioners."--
Keywords: NORAD; Geschichte; Geopolitik; North American Aerospace Defense Command; Command and control systems / Technological innovations / Canada; Command and control systems / Technological innovations / United States; Geopolitics / History / 21st century; Commandement militaire / Innovations / Canada; Commandement militaire / Innovations / États-Unis; Géopolitique / Histoire / 21e siècle; Command and control systems / Technological innovations; Geopolitics; Canada; United States; 2000-2099; History